Analisis Kebijakan Intervensi Spesifik dan Sensitif dalam Penanganan Stunting di Kota Semarang - Karmanis Karmanis; Ainun Ganisia (Jurnal Media Administrasi, 2026)
Stunting is one of the chronic nutritional problems that remains a major challenge in health development in Indonesia. This condition not only affects children’s physical growth but also influences cognitive development, productivity, and the quality of human resources in the future. The government has developed various policies to accelerate the reduction of stunting through specific and sensitive intervention approaches implemented in an integrated manner across sectors. Semarang, as one of the urban areas in Indonesia, has also implemented these policies through various health, nutrition, sanitation, and community empowerment programs. This study aims to analyze the policies of specific and sensitive interventions in addressing stunting in Semarang and to identify factors influencing the effectiveness of their implementation. This research uses a qualitative approach with a policy study method through document analysis, observation, and interviews with relevant stakeholders such as the health office, community health centers, and other local government agencies. Data analysis was conducted descriptively by examining program integration, inter-agency coordination, and community participation in policy implementation. The results show that the implementation of specific and sensitive intervention policies in Semarang has been carried out through various programs such as maternal and child nutrition services, improved access to sanitation, health education, and family empowerment. However, several challenges remain, including suboptimal cross-sector coordination, limited resources, and varying levels of public understanding regarding stunting prevention. Therefore, strengthening policy governance, improving synergy among institutions, and enhancing community participation are necessary to ensure that efforts to accelerate stunting reduction can be implemented more effectively and sustainably.